2020
DOI: 10.3390/pathogens9070571
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Growth and Cell Cycle Progression are Dependent on (p)ppGpp Synthetase/Hydrolase in Brucella abortus

Abstract: Brucella abortus is a pathogenic bacterium able to proliferate inside host cells. During the first steps of its trafficking, it is able to block the progression of its cell cycle, remaining at the G1 stage for several hours, before it reaches its replication niche. We hypothesized that starvation mediated by guanosine tetra- or penta-phosphate, (p)ppGpp, could be involved in the cell cycle arrest. Rsh is the (p)ppGpp synthetase/hydrolase. A B. abortus ∆rsh mutant is unable to grow in minimal medium, it is unab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In Brucella spp., where the G1-phase cell is the primary infectious form (8), synthesis of (p)ppGpp is required for proliferation in phagocytic cells and for survival in mice (73, 74). Conversely, overproduction of (p)ppGpp results in an accumulation of G1-phase cells in the population (75). In Rhizobia spp., mutants lacking (p)ppGpp are severely impacted in their ability to enter into a symbiotic relationship with the leguminous host plant (76, 77) whereas (p)ppGpp overproduction due to nitrogen deprivation delays the G1/S phase transition (78).…”
Section: Discussionmentioning
confidence: 99%
“…In Brucella spp., where the G1-phase cell is the primary infectious form (8), synthesis of (p)ppGpp is required for proliferation in phagocytic cells and for survival in mice (73, 74). Conversely, overproduction of (p)ppGpp results in an accumulation of G1-phase cells in the population (75). In Rhizobia spp., mutants lacking (p)ppGpp are severely impacted in their ability to enter into a symbiotic relationship with the leguminous host plant (76, 77) whereas (p)ppGpp overproduction due to nitrogen deprivation delays the G1/S phase transition (78).…”
Section: Discussionmentioning
confidence: 99%
“…During the first steps of Brucella trafficking, the bacteria is able to block the progression of its cell cycle, remaining at the G1 stage for several hours, before it reaches its replication niche. The work of Van der Henst et al [ 7 ] demonstrated that starvation mediated by guanosine tetra- or penta-phosphate, (p)ppGpp, is one of the factors contributing to G1 arrest observed in B. abortus infection in macrophages. Adhesion to target cells is another major step forward for bacterial invasion and replication.…”
mentioning
confidence: 99%